VD_FINDINFO HC / 2011 / 197 vom 13. April 2011 - VD Tribunal cantonal (2011)
BIEN-FONDS, MOYEN DE DROIT CANTONAL, INTERDICTION, VOIE DE DROIT, PROCÉDURE | 39 al. 1 let. c CPC, 420 CPC, 489 CPC, 29 Cst., 319 CPC (CH), 404 CPC (CH)